2017
DOI: 10.1186/s13578-017-0163-5
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Senp1 promotes mouse early folliculogenesis by regulating BMP4 expression

Abstract: BackgroundMammalian folliculogenesis, maturation of the ovarian follicles, require both growth factors derived from oocyte and surrounding cells, including stromal cells. However, the mechanism by which stromal cells and derived factors regulate oocyte development remains unclear.ResultsWe observed that SENP1, a small ubiquitin-related modifier (SUMO)-specific isopeptidase, was expressed in sm22α-positive stromal cells of mouse ovary. The sm22α-positive stromal cells tightly associated with follicle maturation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 38 publications
0
12
1
Order By: Relevance
“…Scale bars: 20 mm (A and E) and 2.0 mm (C). number and size during early oocyte development, leading to premature ovarian failure in late stages of ovulating life (Tan et al, 2017). However, here, we demonstrate that estradiol can stimulate endometrial hyperplasia in ovariectomized SENP1smKO mice, eliminating the possibility that these effects derive from the ovary.…”
Section: Figure 7 Era Mediates Stem Cell Proliferation and Uterine Hyperplasia In Senp1smko Micecontrasting
confidence: 51%
See 2 more Smart Citations
“…Scale bars: 20 mm (A and E) and 2.0 mm (C). number and size during early oocyte development, leading to premature ovarian failure in late stages of ovulating life (Tan et al, 2017). However, here, we demonstrate that estradiol can stimulate endometrial hyperplasia in ovariectomized SENP1smKO mice, eliminating the possibility that these effects derive from the ovary.…”
Section: Figure 7 Era Mediates Stem Cell Proliferation and Uterine Hyperplasia In Senp1smko Micecontrasting
confidence: 51%
“…We observe endometrial hyperplasia and even endometrial cancer in aged SENP1smKO mice. Previously in SENP1smKO mice, we have observed delayed oocyte growth and follicle maturation with reduced follicle number and size during early oocyte development, leading to premature ovarian failure in late stages of ovulating life ( Tan et al, 2017 ). However, here, we demonstrate that estradiol can stimulate endometrial hyperplasia in ovariectomized SENP1smKO mice, eliminating the possibility that these effects derive from the ovary.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…BMP members BMP4 and BMP7 have been reported to promote primordial to primary follicle transition and a BMP4 antibody dramatically reduces the number of primordial follicles in the rat (Lee et al, 2004; Nilsson & Skinner, 2003). Recently, one study showed stromal cell‐specific knockout Senp1 , a small ubiquitin‐related modifier (SUMO)‐specific isopeptidase, attenuated follicle formation by markedly downregulated expression of BMP4 (Tan et al, 2017). Here, our study not only identified Bmpr1b as the DE gene and Id2 as the key regulon in oocytes but also demonstrated the regulation of BMPs on ID2 through the PI3K/mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Progrowing, primordial follicles do not have an independent capillary network, and they depend on their proximal stromal vessels . Not only vessels, but also stromal cells themselves are involved in promoting early folliculogenesis . Stromal cells have been described to have an important role in follicular survival and growth .…”
Section: Resultsmentioning
confidence: 99%